A challenging case of total hip arthroplasty in a hemodialysis patient having avascular necrosis of femoral head - Kundu, Sujoy (Indian Journal of Case Reports, 2018)
Avascular necrosis (AVN) is an uncommon complication of hemodialysis. Total hip arthroplasty (THA) is the chosen treatment modality in patients suffering from late-stage AVN of the femur; however, performing THA in a hemodialysis patient is challenging. This article describes a case of bilateral late stage AVN of the femoral head in a patient with a failed renal transplant, currently on hemodialysis. To the best of our knowledge, this is the first report of THA in such a patient. A 46-year-old female patient presented with complaints of pain in the hip joint radiating to the groin and anterolateral aspect of the thigh. She was bedridden and suffering from renal failure at the time of presentation and was undergoing hemodialysis for the same. Her history revealed a failed renal transplant. The diagnosis was done with the help of radiographs and magnetic resonance imaging scan which showed bilateral AVN of femur. We conducted THA for both the hip joints at an interval of 6 months. The patient recovered in an uneventful manner and at the time of discharge, the patient could walk without a walker.